ON CERTAIN NON-HUMAN SIMILARITIES IN TYPOLOGY (IN THE EXAMPLE OF BIOLOGY) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article highlights the issues of biological evolution and biological taxonomy in biological science in understanding the problems of language development and genetic description of language.